Geologic Controls on Erosion Mechanism on the Alaska Beaufort Coast - Ravens, Thomas M.; Peterson, Sasha (Frontiers in Earth Science, 2021)
Two prominent arctic coastal erosion mechanisms affect the coastal bluffs along the North Slope of Alaska. These include the niche erosion / block collapse mechanism and the bluff face thaw / slump mechanism. The niche erosion / block collapse erosion mechanism is dominant where there are few coarse sediments in the coastal bluffs, the elevation of the beach below the bluff is low, and there is frequent contact between the sea and the base of the bluff. The bluff face thaw / slump mechanism is dominant where significant amounts of coarse sediment are present, the elevation of the beach is high, and contact between the sea and the bluff is infrequent. We show that a single geologic parameter, coarse sediment aerial density, is predictive of the dominant erosion mechanism and is somewhat predictive of coastal erosion rates. The coarse sediment aerial density is the dry mass (g) of coarse sediment (sand and gravel) per horizontal area (cm2) in the coastal bluff. It accounts for bluff height and the density of coarse material in the bluff. When the aerial density exceeds 120 g cm-2, the bluff face thaw / slump mechanism is dominant. When the aerial density is below 80 g cm-2, niche erosion / block collapse is dominant. Coarse sediment aerial density also controls the coastal erosion rate to some extent.